Build a program now! - Pelland, Patrice (Microsoft Press, 2005)
In this lively, eye-opening, and hands-on book, all you need is a computer and the desire to learn how to program with Visual Basic 2005 Express Edition. Featuring a full working edition of the software, this fun and highly visual guide walks you through a complete programming project-a desktop weather-reporting application-from start to finish. You'll get an introduction to the Microsoft Visual Studio® development environment and learn how to put the lightweight, easy-to-use tools in Visual Basic Express to work right away-creating, compiling, testing, and delivering your first ready-to-use program. You'll get expert tips, coaching, and visual examples at each step of the way, along with pointers to additional learning resources.